Paradigm Secular of Thought in Contemporary Siyasah Jurisprudence - Khairudin Nor; Nugroho Nugroho; Ahmad Zaky Kurniawan; Ahmad Zidane Jauhari; Ahmad Ade Inaya; Surya Sukti (Jurnal Teologi Islam, 2026)
This article discusses the paradigm of secular thought in contemporary Islamic jurisprudence (fiqh siyasah) by examining the dynamics of modern Islamic political thought, the position of the state as a domain of ijtihadiyah, and the evolving forms and models of secular thought. The background to this study is based on significant changes in Islamic political discourse, which are increasingly influenced by modernization, globalization, and interaction with Western political systems. In this context, a tendency has emerged among some Muslim thinkers to adopt a secular approach in understanding the relationship between religion and the state. This research uses a qualitative method with a library research approach, drawing on classical and contemporary literature related to Islamic jurisprudence and secularism. The analysis is conducted descriptively and analytically to identify the characteristics of the paradigm of contemporary Islamic political thought, explain the state as a domain of ijtihadiyah (intelligible text), and examine the forms and models of secular thought in Islamic jurisprudence (fiqh siyasah). The results indicate that contemporary Islamic political thought is dynamic and pluralistic, with a shift from a normative approach to a more contextual and rational one. State governance is understood as part of ijtihadiyah, thus allowing for various forms of government systems suited to the needs of society. Meanwhile, the secular paradigm in contemporary Islamic jurisprudence (fiqh siyasah) is characterized by a functional distinction between religion and the state, as well as an emphasis on universal values such as justice and the welfare of the people. This paradigm has developed into several models, including moderate, substantive, liberal, and integrative-contextual secularism. Thus, it can be concluded that the secular paradigm of thought in contemporary Islamic jurisprudence (fiqh siyasah) represents a form of intellectual adaptation to the challenges of the times, opening up space for renewal in Islamic political thought, while still generating debate regarding the boundaries between secular values and sharia principles.